(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Currently, the issue of accidents and occupational diseases in the automotive industry in Uzbekistan is receiving increased attention, but although the problem is being solved, it is difficult to provide accurate statistical reports. However, it is possible to analyze the main trends and challenges in the last five years (2019–2024). The article analyzes the statistics of accidents and occupational diseases in the automotive industry in Uzbekistan for the last five years and recommends measures developed on this basis.